An Update on Renal Artery Denervation and Its Clinical Impact on Hypertensive Disease. (1st October 2015) - Bhat, Aditya; Kuang, Ye Min; Gan, Gary C. H.; Burgess, David; Denniss, Alan Robert
Abstract : Hypertension is a globally prevalent condition, with a heavy clinical and economic burden. It is the predominant risk factor for premature cardiovascular and cerebrovascular disease, and is associated with a variety of clinical disorders including stroke, congestive cardiac failure, ischaemic heart disease, chronic renal failure, and peripheral arterial disease. A significant subset of hypertensive patients have resistant hypertensive disease. In this group of patients, catheter-based renal artery denervation has emerged as a potential therapy, with favourable clinical efficacy and safety in early trials. Additional benefits of this therapy are also being identified and include effects on left ventricular remodeling, cardiac performance, and symptom status in congestive cardiac failure. Utility of renal denervation for the management of resistant hypertension, however, has become controversial since the release of the Symplicity HTN-3 trial, the first large-scale blinded randomised study investigating the efficacy and safety of renal artery denervation. The aim of this paper is to evaluate the history, utility, and clinical efficacy of renal artery denervation technology, including an in-depth appraisal of the current literature and principal trials.